Reading from the perspective of discourse analysis: building effects of meaning through interdiscursivity (Research, Society and Development, 2020)
This study aims to present and discuss a didactic proposal that deals with language as sociais practices, from the perspective of Discourse Analysis of the French line.  In this perception, we discuss the importance of developing reading strategies based on the concepts of social subject, reading and speech, addressed by the authors, respectively, Foucault, Brandão and Orlandi.  For methodological procedures, we rely on action research, described by Thiollent, with a qualitative approach, according to Bortoni-Ricardo, as we plan to understand the learning difficulties in a given social context and develop resources that can modify the reality of those involved in this process.  In this way, we aim to favor the teaching-learning process of competences and reading skills of students of Basic Education, especially those of Elementary Education, final years.  As a result, we observed the effective participation of the students present in the classes, as well as skills with oral and written use of the Portuguese language, understanding of information implicit in the text and construction of meanings from the readings of the texts presented and discussed in the classroom.